Becoming The Self Without Cigarettes: A Hermeneutic Phenomenological Interpretation Of Ex-Smokers' Life Experiences - Alimin Hamzah; Yusriani Yusriani; Arman Arman (Bajang Institute, 2026)
Quitting smoking is a process of behavior change that is not only related to quitting cigarette consumption, but also involves changing the way individuals understand their body, self, social environment, and life. This research aims to understand the life experiences of individuals during the process of changing smoking cessation behavior and interpret the meaning of these changes in the formation of a new self-identity. This study uses a qualitative method with a hermeneutic phenomenological approach. The research participants consisted of seven lecturers from the Faculty of Sports and Health Sciences, State University of Makassar who had direct experience in the process of quitting smoking. Data were collected through reflective in-depth interviews and analyzed using the process of hermeneutic phenomenological interpretation through in-depth readings, hermeneutic circles, identification of meaningful themes, and researcher reflexivity. The results of the study show that the experience of quitting smoking is a journey of self-transformation that takes place gradually. Four main meanings are found in the participants' experiences, namely the body as the initial space for the emergence of awareness of change, changes in the individual's relationship with himself, the transformation of the world of life through changes in the environment and social relations, and the process of becoming a new self after quitting smoking. Cigarettes that were previously part of routines, social experiences, and individual identities slowly change their meaning as participants find new ways of understanding their health, abilities, and life direction. This study concludes that quitting smoking is not just a change from smoking behavior to non-smoking, but is an existential transformation process that changes the way individuals are in their lives. These findings affirm the importance of a health promotion approach that is not only oriented towards the delivery of health risk information, but also pays attention to life experiences, personal meaning, and the process of forming an individual's new identity in living a life without smoking.